Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
f=8
Step-by-step explanation:
0.62(f+(-6)+6.96=8.2
0.62(f-6)+6.96=8.2
multiply both sides by 100
0.62(f-6)*100+6.96*100=8.2*100
Refine
62(f-6)+696=820
Subtract 696 from both sides
62(f-6)+696-696=820-696
Simplify
62(f-6)=124
Divide both sides by 62
62(f-6)/62 = 124/62
Simplify
f-6=2
add 6 to both sides
f-6+6=2+6
simplify
f=8
Answer:
8
Step-by-step explanation:
1. Distribute 0.62 to each term in the parenthesis:
0.62(f) + 0.62(-6)
0.62f - 3.72 + 6.96 = 8.2
2. Add 3.72 and 6.96:
0.62f - 3.72 + 6.96 = 8.2
0.62f + 3.24 = 8.2
3. Subtract 3.24 from both sides of the equation:
0.62f + 3.24-3.24 = 8.2-3.24
0.62f = 4.96
4. Divide 0.62 by both sides to isolate f:
0.62f/0.62 = 4.96/0.62
f = 8
hope this helps!
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.